Frontiers in algorithmics and algorithmic aspects in information and management Joint International Conference, FAW-AAIM 2011, Jinhua, China, May 28-31, 2011 : proceedings - FAW-AAIM 2011 (Conferência) (Lectures notes in computer science, 2011)
This book constitutes the refereed proceedings of the 5th International Frontiers of Algorithmics Workshop, FAW 2011, and the 7th International Conference on Algorithmic Aspects in Information and Management, AAIM 2011, jointly held in Jinhua, China, in May 2011. The 35 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 92 submissions. The papers cover a wide range of topics in the areas of algorithmics, combinatorial optimization and their applications presenting current trends of research.